Métodos de Financiamiento para PYMES. - Molina León, Cendy Katerin; Ruiz Quintero, Cristian Leonardo (Corporación Universitaria Minuto de Dios, 2020)
Este proyecto es elaborado para brindar un apoyo al gran mercado de las empresas Pymes, las cuales por problemas financiaron y de poco conocimiento en el área, terminan cerrando sus compañías en los primeros años de funcionamiento. Por lo tanto, el trabajo busca determinar ¿Cuál es el tipo de financiación que brinda mejores ventajas a las empresas pymes en sus primeros tres años de funcionamiento?, teniendo esta base de investigación se encuentran un alto número de posibilidades de apoyo tanto financiero como para la organización, el cual promueve que las empresas tengan un crecimiento sostenible y sustentable. Para este fin también se debe tener en cuenta ¿cómo esta creada la compañía?, ¿Cuál es su actividad económica?, ¿cuál es la ciudad en donde esta ubicada? Estas preguntas son la base de encontrar la mejor opción en calidad de apoyo.

During the last years the economy has generated different markets, for which the activities that are generated by anenter priseor a business idea are affected, because they do not have a stable financial support to enter to compete in a specific sector. Of the economy, apart from not having a sustainable and sustainable growth, however the financingis given through credits for microentrepreneurs, these are influenced by factors such as operating and operating expenses, remodeling or adaptations, including the purchase or lease of property plant and equipment; According to the Global Entrepreneurship Monitor (GEM), it is recognized that in the see cosystems the differents tages ofentre preneurship are not always sencouraged wi the qualforce: incubation, management, and the stage of maturity or consolidation. The current organizations have had a significant evolution in all areas of application, within whichit is note worthy that financingis a point that has a great variation in the decision making of companies. There fore, this area be comes one ofthe most important when startingan SME. In “Recentre search by the McKinsey Global Institute reveale d that there are 200 million small and medium-sized companies in the world that do not have access to credit services. (Economica, 2018) Investment in Colombia is not in high demand for SMEs, because private investment has not been enough to finance different business projects and attract international attention. In Colombia, 90% ofthe companies that are incorporated are SMEs, small and medium, which generate about 60% of jobs and represent only 30% of the country's gross domestic product (GDP). (Gomez, 2019) This is large ly dueto the fact that a significant percentage of SMEs do notachieve sufficient growth to continue operating, because they do not have an adequate financingsy stem which will lead them to have a project in the ir firsty ears sustainable and sustainable.
Identificar los métodos de financiación que beneficien el crecimiento de las empresas Pymes en Colombia, de acuerdo con su actividad comercial, a fin de minimizar los riesgos y evitar la disminución de su rentabilidad.
Keywords: Pymes; Créditos; Financiamiento; Financing; Loans for Entrepreneurs; Financingis; Financiamiento de empresas; Finanzas corporativas; Gestión financiera